Exploring Patterns of the Use of Electronic Nicotine Delivery Systems among Adolescents in High-Risk Appalachian (U.S.A) Communities. (28th January 2022) - Mamudu, Hadii M.; Shahani, Disha; Jones, Antwan; Ahuja, Manik; Adeniran, Esther; Weierbach, Florence; Swindle, Jean; Liu, Ying; Keener, Janet; Blair, Cynthia J.; McNabb, Michelle; Asare, Matthew; et al.
ABSTRACT: Background: Electronic nicotine delivery systems (ENDS) use among adolescents in the United States (U.S.) has surpassed conventional tobacco products (CTPs), including cigarettes. Increasingly, ENDS are used concurrently with CTPs and substances such as cannabis. However, few studies involve Central Appalachia, a region with historically high rates of tobacco and other substance use. Objective: To examine prevalence of concurrent use of ENDS and cannabis among school-going adolescents in Appalachian Tennessee and delineate associations between ENDS use and substance-related risk behavior (cannabis use), social relations (peer use), and school-related risk behavior (academic performance). Methods: Data were obtained from a survey conducted with youth aged 13-17 years in 2018 in a county in Appalachian Tennessee ( n = 280). A multivariable logistic regression model was fit to evaluate associations between ENDS and cannabis use, and other factors. Results: Overall, lifetime ENDS and cannabis prevalence estimates were 31.1% and 18.6%, respectively. Lifetime ENDS users had increased odds of also being lifetime cannabis users [OR = 9.22, 95% confidence interval (CI): 3.44-24.75]. Lifetime ENDS users had increased odds of reporting ENDS use among peers [OR = 12.11; 95% CI: 5.40-27.12] and lower academic performance (OR associated with mostly C or D vs. A grades was 4.28, 95% CI: 1.68-10.90). Conclusion : This study found an association between ENDS and cannabis use among adolescents in Appalachian Tennessee exists. Additionally, peer use and academic performance were associated with ENDS use. The findings have implications for public health intervention planning to address not only ENDS but also substance use among Appalachian youth.